2021
DOI: 10.2147/copd.s332613
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Infusion of Bone Marrow and Mesenchymal Stromal Cells in Patients with Chronic Obstructive Pulmonary Disease: Phase I Randomized Clinical Trial

Abstract: Background and Objectives Chronic obstructive pulmonary disease (COPD) is characterized by the destruction of alveolar walls, chronic inflammation and persistent respiratory symptoms. There is no curative clinical treatment for COPD. In this context, cell-based therapy is a promising therapeutic alternative for COPD. Thus, in this open, controlled and randomized Phase I Clinical Trial, we aimed to assess the safety of the infusion of autologous bone marrow mononuclear cells (BMMC), adipose-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…Of the 415 potentially relevant records identified in the initial search, 14 studies [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were deemed eligible for a qualitative synthesis. Since 3 studies [ 48 , 49 , 50 ] reported non-extractable data on efficacy outcomes, the quantitative synthesis (pairwise meta-analysis) was carried out on 11 studies [ 46 , 47 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 415 potentially relevant records identified in the initial search, 14 studies [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were deemed eligible for a qualitative synthesis. Since 3 studies [ 48 , 49 , 50 ] reported non-extractable data on efficacy outcomes, the quantitative synthesis (pairwise meta-analysis) was carried out on 11 studies [ 46 , 47 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 415 potentially relevant records identified in the initial search, 14 studies [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] were deemed eligible for a qualitative synthesis. Since 3 studies [ 48 , 49 , 50 ] reported non-extractable data on efficacy outcomes, the quantitative synthesis (pairwise meta-analysis) was carried out on 11 studies [ 46 , 47 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. The effect estimates of the pairwise meta-analysis were obtained from 371 COPD patients selected from 6 non-randomized, non-controlled clinical trials [ 46 , 47 , 52 , 53 , 54 , 55 ], 3 RCTs [ 56 , 57 , 58 ], and 2 observational cohort studies [ 51 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations